Biographical risks and their impact on uncertainty in fertility expectations: A gender-specific study based on the German Family Panel - Anne-Kristin Kuhnt; Petra Buhr (Universität Duisburg-Essen, Institut für Soziologie, 2016)
This paper studies uncertainty in fertility expectations from a life course perspective. Our research hypotheses are theoretically based on Life Course Theory and the Theory of Planned Behavior. We assume that biographical risks, inferred from separation from partner, unemployment or changes in parity, lead to uncertainty in women's and men's fertility expectations. We also assume gender-specific differences regarding the effect of these risks, because the life courses of women and men still differ substantially regarding paid and domestic work. Data come from waves 1-6 of the German Family Panel. We apply fixed effects multinomial logit models. Our findings confirm that uncertainty in fertility intentions is of relevant prevalence in our sample and is not stable over the life course. In accordance with our hypotheses, uncertainty is connected with changes in partnership status, employment status, and parity of children. Furthermore, gender-specific differences emerge. While separation is stronger associated with uncertainty for men than for women, unemployment is more strongly associated with uncertainty among women. However, our findings provide no support for gender-specific differences regarding an increase in uncertainty after the transition to first birth. – – Dieser Beitrag untersucht Ausmaß und Ursachen von Unsicherheit in Hinblick auf die erwartete Kinderzahl von Männern und Frauen. Auf der Grundlage des Lebenslaufsansatzes und der Theorie des geplanten Verhaltens nehmen wir an, dass biographische Risiken in Zusammenhang mit einer Trennug vom Partner, Arbeitslosigkeit oder der Geburt von Kindern Unsicherheit in Hinblick auf die erwartete Kinderzahl von Frauen und Männern nach sich ziehen. Darüber hinaus vermuten wir geschlechtsspezifische Unterschiede in Hinblick auf den Einfluss dieser Faktoren, da sich der Lebensverlauf von Männern und Frauen noch immer substantiell hinsichtlich Erwerbs- und Hausarbeit unterscheidet. Wir nutzen Daten der ersten sechs Wellen des deutschen Beziehungs- und Familienpanels (pairfam) und verwenden fixed effects multinomial logit Modelle. Unsere Ergebnisse zeigen, dass Unsicherheit in Hinblick auf die erwartete Kinderzahl ein relevantes Phänomen und zudem nicht stabil im Lebensverlauf ist. Entsprechend unserer Hypothesen steht Unsicherheit im Zusammenhang mit Veränderungen in verschiedenen Lebensbereichen. Darüber hinaus zeigen sich geschlechtsspezifische Differenzen. Während eine Trennung einen stärkeren Effekt bei Männern als bei Frauen hat, ist der Effekt von Arbeitslosigkeit auf Unsicherheit in Bezug auf die erwartete Kinderzahl bei Frauen größer. Beim Übergang zum ersten Kind zeigen sich dagegen keine geschlechtsspezifischen Unterschiede.
urn:nbn:de:hbz:464-20161128-152923-9
Keywords: 300; Fertility expectations; Uncertainty; Biographical risks; Gender-specific differences; Erwartete Kinderzahl; Unsicherheit; Biograpgische Risiken; geschlechtsspezifische Unterschiede